Social Vulnerability in Flood Disaster Preparedness: A Narrative Review - Ratna Puji Priyanti; Asri; Iswanto; Nurul Hidayah; Sakti Oktaria Batubara; Eva Fellipe Dimog (UPPM STIKES Pemkab Jombang, 2025)
Flood disasters remain among the most common and destructive hazards worldwide, with climate change and rapid urbanization intensifying both hazard severity and susceptibility. This narrative review synthesizes factual and conceptual advancements concerning societal vulnerability in the context of flood catastrophe preparedness. The review integrates peer-reviewed studies and relevant technical and institutional literature, consolidating dominant definitions of vulnerability as a function of exposure, sensitivity, and adaptive capacity, while considering recent developments that situate vulnerability within integrated Social–Ecological–Technological Systems (SETS). This analysis examines key assessment frameworks and tools, including Social Vulnerability Indices (SVIs), the MOVE framework, and the Flood Resilience Measurement for Communities (FRMC), highlighting the use of indicator-based methodologies to pinpoint vulnerability hotspots and inform decision-making. Evidence demonstrates that socioeconomic disadvantage, demographic characteristics, social capital, and institutional capacity consistently affect disparities in flood damage and recovery trajectories, often through intersectional and location-specific mechanisms. The review contends that equitable disaster risk reduction requires the integration of vulnerability metrics into planning and investment, the improvement of methodological transparency and local relevance of indicators, and the strengthening of social protection, inclusive risk communication, and accountable governance to transform assessments into concrete, actionable interventions.